ENGLISH VOCABULARY ACQUISITION OF SEVEN YEARS OLD CHILDREN AT PRIMARY SCHOOL - Fauziah Aquila Br. Purba; Sumarsih Sumarsih (Universitas Negeri Medan, 2022)
This study aimed to describe learning strategies and the factors that influence the mastery of English vocabulary in children aged 7 years in primary school. In conducting this research, the researcher did it at SD Swasta Salsa. The researcher used the descriptive qualitative method to analyze the data. Researchers found several learning strategies used by students in the teaching and learning process of English in the classroom with several methods used by the teacher. The result of this research is that it is easier for students to accept English vocabulary by using cognitive strategies in translating. Because the first language of students and teachers is Bahasa, and English is their second language. So after they repeat the English vocabulary, they also translate it into Bahasa and vice versa. In addition, two factors namely internal factors and external factors are also factors in obtaining English vocabulary for SD Swasta Salsa Students. First, internal factors namely age, learning styles, and intrinsic motivation. Second, external factors namely the classroom climate, curriculum, culture and status, external motivation, instruction, and also the formal situation. Children with a good influence factor of English vocabulary will most likely easily get English vocabulary.Key words : Vocabulary acquisition, Children Language Acquisition, Vocabulary Learning Strategies, Factor Influences